Brønsted Acid Catalyzed Stereospecific Dearomative Spirocyclization of Benzothiophenyl Analogues of Tertiary cis-β-Benzylstyrenes - Tohti, Anargul; Lerda, Victoria; Stokes, Benjamin J. (Synlett, 2024)
3-Substituted benzothiophenyl analogues of tertiary cis-β-benzylstyrenes undergo triflic acid catalyzed dearomative spirocyclization at room temperature to afford compounds containing vicinal quaternary centers. Hydroarylation of the styrene is a competing process that occurs preferentially within substrates possessing electron-rich styrenyl alkenes, or an indole in place of the benzothiophene.
Keywords: quaternary carbons; spiroheterocycles; dearomatization; spirocyclization; Brønsted acid catalysis; hydroarylation